Rethinking the Public Fetus Historical Perspectives on the Visual Culture of Pregnancy - Björklund, Elisabet; Jülich, Solveig (Rochester Studies in Medical History, 2024)
Exploring a wide variety of visualizations of pregnancy and fetuses through 300 years of history, this timely volume offers a fresh look at the influential feminist concept of the "public fetus." Images of pregnant and fetal bodies are today visible everywhere. Through ultrasound screenings at maternity clinics, birth videos on social media platforms, or antiabortion propaganda, visualizations of pregnancy are available and accessible as never before. The origins of today's visual culture of pregnancy are often traced back to the 1960s, when Swedish photographer Lennart Nilsson's stunning photographs of human development were published in Life magazine and widely disseminated over the world. But the public display of pregnant and fetal bodies actually has a much longer and more complex history. In this timely book, a group of scholars from a range of disciplines explores this multifaceted history by highlighting visualizations of pregnant and fetal bodies in a variety of geographical and cultural contexts, spanning a period of more than 300 years. By reengaging with the crucial concept of the "public fetus," coined by feminist scholars in the 1980s and 1990s, the volume aims to revitalize the scholarly discussion on the visual culture of pregnancy and demonstrate the constructed nature of fetal images. Including chapters on a wide variety of representations in different media, such as wet specimen collections, papier-mâché models, sculpture, film, and photography, the book provides a much-needed argument against the widespread notion of the "universal" fetus. On publication this title is available as an Open Access ebook under the Creative Commons License: CC-BY-NC-ND.